Employment of doctors of veterinary medicine from 2010-2019 - Cvitković, Denis; Volarević, Boris; Tadić, Marko, veterinar; Pašić, Selim; Pavlak, Marina, veterinarka (2020)
The employment of veterinarians is an indicator of economic development and of the quality of the relationship between humans and nature. Several authors have published reports on the employment of veterinarians. This paper examines the trends in unemployment and employment of veterinarians according to the records of the Croatian Employment Service (CES) in the period from 2010 to 2019. The CES is a public institution of the Republic of Croatia established under the Labour Market Act (Official Gazette 118/18) that plays a key role in regulating supply and demand on the labour market of the Republic of Croatia. The average number of employed veterinarians was higher than the average number of veterinarians registered in the CES records. An average of 181 veterinarians were sought annually, 160 were employed and 143 were registered, indicating that demand surpassed supply. Veterinarians were recruited faster than the average person with a college degree, within 180 days, and very few were in longterm unemployment. Most were employed in the category of young people (up to 30 years of age), and most were employed without any previous work experience. More women than men were employed. Most veterinarians were employed in the City of Zagreb, which reflects the relatively low livestock production and depopulation of rural areas, as the traditionally main and safest source of employment for veterinarians. According to the National Classification of Economic Activities (NKD), veterinarians were employed in almost all groups of activities, allowing for greater employment flexibility and mobility on the labour market. According to the National Classification of Occupations (NKZ), on the other hand, most veterinarians were employed in group 2 (experts and scientists), likely since veterinary medicine is a regulated profession. This also means that several were employed under their qualification levels.
Zapošljavanje veterinara jedan je od pokazatelja smjera razvoja gospodarstva i kvalitete odnosa čovjeka i prirode od koje živi. O zaposlenosti veterinara već su u nekoliko navrata pisali neki autori. U ovome radu željeli smo ustvrditi kakva su kretanja nezaposlenosti i zapošljavanja veterinara prema podatcima iz evidencije Hrvatskog zavoda za zapošljavanje (HZZ) u razdoblju od 2010. - 2019. HZZ je javna ustanova u vlasništvu Republike Hrvatske ustrojena Zakonom o tržištu rada (Narodne novine 118/2018) i ima ključnu ulogu u reguliranju ponude i potražnje na tržištu rada Republike Hrvatske. Prosječan broj zapošljavanih veterinara bio je veći od prosječnog broja veterinara registriranih u evidenciji HHZ-a. Godišnje je prosječno tražen 181 veterinar, zapošljavano ih je 160, a prijavljivano 143. Potražnja za veterinarima bila je veća od ponude. Veterinari su se zapošljavali brže od prosjeka zapošljavanja osoba s fakultetskom diplomom, većinom u roku do 180 dana te ih je vrlo mali broj bio u dugotrajnoj nezaposlenosti. Najviše ih je zapošljavano u kategoriji mladih (do 30 godina), a najviše su se zapošljavali oni bez radnog staža. Zapošljavano je više žena nego muškaraca. Najviše ih je zapošljavano u Gradu Zagrebu, što je istovremeno odraz razmjerno niske stočarske proizvodnje i depopulacije ruralnih područja koja su tradicionalno glavni i najsigurniji izvor zapošljavanja za veterinare. Prema Nacionalnoj klasifikaciji djelatnosti (NKD) veterinari su se zapošljavali u gotovo svim skupinama djelatnosti što im omogućava veću fleksibilnost zapošljavanja i veću mobilnost na tržištu rada. Prema Nacionalnoj klasifikaciji zanimanja (NKZ), najviše se veterinara zapošljavalo u rodu 2 (stručnjaci i znanstvenici), vjerojatno zato što je veterinarstvo regulirana profesija. To istovremeno znači da ih se mali broj zapošljavao na razinama obrazovanja nižima od stečene.
Bibliografija: 31 jed.
Summary ; Sažetak.
Keywords: Veterinari -- Tržište rada -- Zapošljavanje